The Effect of Credit Risk and Interset Rate Risk on Microfinance Institution's Financial Sustainability: The Case of Middle Java Conventional Bank Perkreditan Rakyat with Three Different Categories of Assets - Idoliany, Findy; Wiryono, Sudarso Kaderi (Journal of Business and Management, 2014)
Abstract â€“ Bank Perkreditan Rakyat (BPR) play very important role in Indonesian economy. Therefore, it is accelerated to always be â€œhealthyâ€. Financial sustainability is one of the critical aspects in microfinance and financial performance is highly correlated with integration and coordination across risk. Therefore, it is important to study the impact of risks towards BPRâ€™s financial sustainability. Major risks in MFIs are asset-liability management risks, which include credit risk, liquidity risk, interest rate risk, and foreign exchange risk. However, BPR do not perform foreign exchange transactions and there are no available data for liquidity risk. But the indicators analyzed and proposed by the author may be used by BPR to monitor their performance. Therefore, the author examines the relationship between credit risk and interest rate risk towards financial sustainability, from 2010 until 2012, in Middle Java BPR with asset below 10 billion rupiah (type A), between 10 to 100 billion rupiah (type B), and above 100 billion rupiah (type C). To determine the relationship, the author uses canonical correlation analysis with cross-sectional data. The result shows that Non-Performing Loan, representing credit risk, has negative and medium significant relationship with financial sustainability in all the cases. Reserve Ratio, representing credit risk, has negative and medium significant relationship with financial sustainability in BPR Asset Type A and C; and negative and low significant relationship in BPR Asset Type B. Net Interest Margin, representing interest rate risk, has positive and low significant relationship with financial sustainability in all the cases. BPR should focus more on managing credit risk.Keywords: Credit Risk, Liquidity Risk, Interest Rate Risk, Asset Liability Management, Microfinance, Bank Perkreditan Rakyat, Financial Sustainability